The Regional Determinants and Policy Implications of Rice Production Volatility in East Nusa Tenggara (Evidence From Fixed-Effects Panel Data Analysis) - Ayu Fitriani; Aplonia Bani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
This study examines the factors influencing rice production volatility in East Nusa Tenggara (NTT) Province, a region marked by severe climatic and geographical constraints that pose challenges to its long-term agricultural stability. As rice is central to national food security and economic stability, understanding its production dynamics in vulnerable regions, such as NTT, is crucial. The province exhibits considerable volatility and disparities in rice production across its 22 districts. This study aims to analyze the influence of harvested area, rainfall, Gross Regional Domestic Product (GRDP) of the agricultural sector, and population on rice production. Employing a quantitative approach, this research uses secondary panel data from 22 districts over the period 2018–2024. Using STATA/SE 17, the analysis applies a Fixed Effects Model (FEM) with a log-log specification to control for unobserved inter-district heterogeneity. The main results show that harvested area and rainfall are the primary factors significantly influencing rice production at the aggregate district level. The elasticity of harvested area is 0.964, underscoring its role as the most critical driver of production. Rainfall, with an elasticity of 0.048, also contributes positively, reflecting the importance of water availability for productivity. In contrast, the Gross Regional Domestic Product (GRDP) of the agricultural sector and population size do not exhibit significant effects within the model. The FEM explains 82.65% of the within-district variation in production, indicating strong explanatory power. These findings suggest that policy efforts should focus on safeguarding productive agricultural land and improving water resource infrastructure to enhance regional food security and farmer welfare in NTT.